2018
DOI: 10.1097/igc.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Activity Behaviors and Physiological Characteristics of Women With Advanced-Stage Ovarian Cancer: A Preliminary Cross-sectional Investigation

Abstract: Posttreatment OC survivors spent more time in prolonged sedentary bouts and had lower cardiorespiratory fitness and upper body strength compared with controls. Moderate and vigorous physical activity was associated with physical function and muscle cross-sectional area. Future studies should test the efficacy of exercise interventions to increase MVPA, reduce sedentary behavior, and increase cardiorespiratory fitness and muscle strength in OC survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The importance of monitoring the physical and psychological side effects of treatment in cancer survivors is also emphasized in recent studies [ 13 15 ]. Although activity behaviors and physical function were compared in a preliminary study conducted with advanced OC survivors and controls [ 16 ], no studies comprehensively evaluated the effects of treatment and/or outcomes of disease processes in early and advanced OC survivors. Therefore, the primary aim of this study was to compare functional status (functional exercise capacity, functional fitness, and muscle endurance) and health-related parameters (peripheral, lower extremity and respiratory muscle strength, physical activity level, fatigue, neuropathy, level of depression and anxiety, and quality of life) of early stage (stage I or II) and advanced stage (III or IV) OC survivors and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of monitoring the physical and psychological side effects of treatment in cancer survivors is also emphasized in recent studies [ 13 15 ]. Although activity behaviors and physical function were compared in a preliminary study conducted with advanced OC survivors and controls [ 16 ], no studies comprehensively evaluated the effects of treatment and/or outcomes of disease processes in early and advanced OC survivors. Therefore, the primary aim of this study was to compare functional status (functional exercise capacity, functional fitness, and muscle endurance) and health-related parameters (peripheral, lower extremity and respiratory muscle strength, physical activity level, fatigue, neuropathy, level of depression and anxiety, and quality of life) of early stage (stage I or II) and advanced stage (III or IV) OC survivors and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer care, physical activity is recommended as an adjunct cancer therapy, with emerging evidence supporting its efficacy in improving physical function and enhancing psychosocial health in women with ovarian cancer [ 14 , 15 ]. Despite the reported benefits of regular participation in physical activity in other cancer groups [ 12 ], recent evidence has found that most women with ovarian cancer are insufficiently physically active following diagnosis [ 15 17 ]. Current guidelines recommend all people diagnosed with cancer participate in 150 min of moderate-intensity aerobic activity and two resistance sessions per week [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disease progression, aggressive treatments, and high rates of recurrence have all been identified to negatively impact physical activity participation in women with ovarian cancer [ 14 , 15 ]. Therefore, there is a clinical need to understand further why many women with ovarian cancer are physically inactive [ 15 , 17 ]. Furthermore, understanding enablers of physical activity participation in this patient group are equally as important to develop delivery models of physical activity that are in keeping with the needs and preferences of women living with ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In OC, suboptimal muscle morphology is highly prevalent and correlates with more post-operative complications and chemotherapy toxicity [ 10 ] and increased mortality [ 11 ]. In a cross-sectional study conducted by our group, we observed significantly lower physical function and upper body strength in post-treatment OC survivors compared with age-matched controls [ 12 ].…”
Section: Introductionmentioning
confidence: 99%